2020
DOI: 10.1007/s00330-020-07034-x
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT practice and protocols for COVID-19 from radiation dose management perspective

Abstract: The global pandemic of coronavirus disease 2019 (COVID-19) has upended the world with over 6.6 million infections and over 391,000 deaths worldwide. Reverse-transcription polymerase chain reaction (RT-PCR) assay is the preferred method of diagnosis of COVID-19 infection. Yet, chest CT is often used in patients with known or suspected COVID-19 due to regional preferences, lack of availability of PCR assays, and false-negative PCR assays, as well as for monitoring of disease progression, complications, and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
118
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 29 publications
0
118
0
2
Order By: Relevance
“…Our study on variations in CT utilization, protocols, and radiation doses demonstrates a lack of There are no specific recommended or target doses in patients with COVID-19 pneumonia, but when evaluation is limited to lung parenchyma, a CTDIvol <3mGy, as recommended for low dose chest CT for lung cancer screening may be sufficient for COVID-19 pneumonia [8]. There are studies on use of high-resolution and ultra-high-resolution chest CT in patients with COVID-19 pneumonia, most studies related to acquisition technique for scanning these patients describe use of non-contrast reduced-dose CT protocol [10,[19][20][21][22].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Our study on variations in CT utilization, protocols, and radiation doses demonstrates a lack of There are no specific recommended or target doses in patients with COVID-19 pneumonia, but when evaluation is limited to lung parenchyma, a CTDIvol <3mGy, as recommended for low dose chest CT for lung cancer screening may be sufficient for COVID-19 pneumonia [8]. There are studies on use of high-resolution and ultra-high-resolution chest CT in patients with COVID-19 pneumonia, most studies related to acquisition technique for scanning these patients describe use of non-contrast reduced-dose CT protocol [10,[19][20][21][22].…”
Section: Discussionmentioning
confidence: 88%
“…But disparities exist in the availability of the preferred diagnostic test, reverse transcription polymerase chain reaction (RT-PCR) for COVID- 19. Also, the high false-negative rate of RT-PCR in early disease and its inability to assess disease severity and progression have led to the growing use of cross-sectional imaging such as CT for diagnosis and assessing disease severity, progression, complications, and treatment response [8]. Although a few single-center studies reported use of chest CT for diagnosis and work-up of patients with COVID-19 pneumonia [9,10], a recent survey suggested that only a very few sites use reduced-dose scan protocols (with lower radiation dose compared to routine or general chest CT protocol) for imaging patients with the suspected or known disease [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, in a previous study evaluating only inspiratory lung volume in the supine and standing positions (with the subject’s arms down) 6 , the acquired CT data could not provide a prediction of the functional residual capacity or inspiratory capacity because of the lack of expiratory CT data. In this study, to perform both inspiratory and expiratory CT, we used a tube voltage of 100 kVp and automatic exposure control with a noise index of 24 for a slice thickness of 5 mm (relatively low-radiation-dose protocol) because the low-radiation-dose CT with recent scanner technology or reconstruction methods is reported to be sufficient to detect lung cancers 28 , nodules 29 , and pneumonia including COVID-19 pneumonia 30 , 31 and because low radiation dose is reported to be unrelated to the volume or area measurement accuracy 32 , whereas a previous study 6 evaluating only inspiratory CT in the supine and standing positions used a tube voltage of 120 kVp and a noise index of 15.…”
Section: Discussionmentioning
confidence: 99%